The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/er.6648
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of hydrogen addition in a passive pre‐chamber ignited SI engine for passenger car applications

Abstract: Hydrogen is one of the most promising alternative fuels for the transportation industry. The use of hydrogen to enable lean burn in internal combustion engines is an attractive solution for reducing CO 2 emissions from two points of views: the substitution of carbon-based fuels and the increased thermal efficiency due to lean operation. Combining this strategy with the passive prechamber ignition system with gasoline/hydrogen blends is even more interesting. The main limitations of the passive pre-chamber conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Several calculations of the complete engine cycle were performed considering different engine speeds (1350, 2500 and 4500 rpm) and fuel compositions (25%, 50%, 75% and 100% of H 2 ). The CFD model setup was obtained from previous works [31,32] that consider the same engine hardware.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several calculations of the complete engine cycle were performed considering different engine speeds (1350, 2500 and 4500 rpm) and fuel compositions (25%, 50%, 75% and 100% of H 2 ). The CFD model setup was obtained from previous works [31,32] that consider the same engine hardware.…”
Section: Methodsmentioning
confidence: 99%
“…The CFD model used for this purpose has been widely used in other investigations [31,32]. Using this configuration, several simulations were performed to obtain the evolution of L t and u along the engine cycle for different engine speeds.…”
Section: Modelling Turbulent Flame Speedmentioning
confidence: 99%
“…Without requiring any modifications, spark ignition engines may run on hydrogen [122]. Higher hydrogen combustion velocity enhances combustion and increases brake thermal efficiency.…”
Section: Spark Ignition Enginesmentioning
confidence: 99%
“…However, it was also shown that increasing the hydrogen fraction in the blend increases NOx levels. In [27] it was shown that the use of hydrogen in SI engines along with a passive prechamber ignition system gives significant benefits in the main chamber combustion process by improving the thermo-chemical characteristics of the mixture, boosting flame speed, and improving flame structure.…”
Section: Introductionmentioning
confidence: 99%